The invention of race : scientific and popular representations - Bancel, Nicolas 1965-; David, Thomas 1967-; Thomas, Dominic (Routledge studies in cultural history, 2018)
This edited collection explores the genesis of scientific conceptions of race and their accompanying impact on the taxonomy of human collections internationally as evidenced in ethnographic museums, world fairs, zoological gardens, international colonial exhibitions and ethnic shows. A deep epistemological change took place in Europe in this domain toward the end of the eighteenth century, producing new scientific representations of race and thereby triggering a radical transformation in the visual economy relating to race and racial representation and its inscription in the body. These practices would play defining roles in shaping public consciousness and the representation of “otherness” in modern societies. The Invention of Race provides contextualization that is often lacking in contemporary discussions on diversity, multiculturalism and race